Friedricho Nietzsche's politinė filosofija kaip politinė antropologija. - Baranova, Jūratė (Problems / Problemos, 2020)
The article starts with the question: how is the political philosophy of Friedrich Nietzsche even possible? The author discusses with Tracy B. Strong's presumption that Nietzsche's political philosophy is not possible as a transcendental deduction. The author supposes that this type of question clashes with the premises of Nietzsche's thinking and also undermines the interpretation of the other aspects of his philosophy. First of all: the question of nazification and denazification of Nietzsche's thought. The article comes to the conclusion that in the scope of recent investigation there is not much sense in raising the question whether Nietzsche's political views are political philosophy in the normative meaning of the term, but it is possible to discuss the question of political anthropology as the psychology of the nations Nietzsche was really interested in.